Sisterhood denied : race, gender, and class in a New South community - Janiewski, Dolores E., 1948- (Class and culture., 1985)
The field of women’s history was flourishing in the 1980s, encouraging the study of more and more aspects of women’s lives, including their paid labor. In 1985 Dolores Janiewski’s Sisterhood Denied: Race, Gender, and Class in a New South Community joined the ranks of books devoted to the study of women’s work and its contribution to the wealth of their communities. Her study of Durham, North Carolina and her focused analysis of the work of both black and white southern women in particular makes Sisterhood Denied a classic of southern labor history and women’s history. Janiewski examined how a “new," industrial South was built in part on women’s labor, explored women’s lives at the intersections, and analyzed the potential for and disconnect in women’s relationships with labor unions, leaving a path for future scholars of southern women workers to follow.